Corporate innovation hubs: from open innovation to ecosystem management function - Barcellos, Filipe Marinho (2023)
Engaging with external communities might reshape organizational attributes and the way firms innovate. Responding to the ambidextrous and open innovation challenge, many firms implement Corporate Innovation Hubs (CIH), separating incremental innovation routines from radical innovation development and engaging with multiple ecosystems. Creating or sustaining focal value propositions in an ecosystem is a challenging managerial task and the research object of the ecosystem management (EM) literature. However, there are limited studies focused on the organizational forms of EM linked to (especially radical) innovation management. Thence, the question that guides this research arises: guiding this inquiry arises: how do ecosystem management functions emerge at ambidextrous units? Firstly, a systematic literature review of the ambidexterity, ecosystem, and radical innovation fields is applied to build a conceptual model of ecosystem orchestration for radical innovation and a typology of ecosystem engagement mechanisms based on ecosystem type, i.e., (1) innovation, (2) entrepreneurial, and (3) knowledge ecosystem. Secondly, an inductive-comparative case study on four firms that launched and developed their own CIH unveils the four building blocks (mandate, orientation, identity, and the dyad structure and processes) of a Corporate Innovation Hub evolving through three phases to an Ecosystem Orchestrator role.